If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2(y + 1) = -1y + 21 Reorder the terms: 5 + -2(1 + y) = -1y + 21 5 + (1 * -2 + y * -2) = -1y + 21 5 + (-2 + -2y) = -1y + 21 Combine like terms: 5 + -2 = 3 3 + -2y = -1y + 21 Reorder the terms: 3 + -2y = 21 + -1y Solving 3 + -2y = 21 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 3 + -2y + y = 21 + -1y + y Combine like terms: -2y + y = -1y 3 + -1y = 21 + -1y + y Combine like terms: -1y + y = 0 3 + -1y = 21 + 0 3 + -1y = 21 Add '-3' to each side of the equation. 3 + -3 + -1y = 21 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 21 + -3 -1y = 21 + -3 Combine like terms: 21 + -3 = 18 -1y = 18 Divide each side by '-1'. y = -18 Simplifying y = -18
| 4(d+6)+1=-1 | | 2*2*2*2-2*8= | | 16x^4+12x^2-8=0 | | 50k+70=40k+90 | | -0.005t=-0.2 | | -5x/6+1=7/18 | | 30k+70=20k+100 | | 295=219 | | 0.75x=7-5x | | 13s-31=2s+l | | 2(2x-4)=-3x-1 | | 2(4z+3)=7z+4 | | 15y+14=2(5+6) | | -15x=128 | | (3x+1)(x+1)(4x+3)= | | 5-9=3(x-3) | | (25x^4)-(15x^2)+2=0 | | 1=1a | | -15x=-28 | | (1)/(2)(6-y)=y | | 300-5=222-3 | | 34=-5-6t+31 | | 4x^5=8 | | 7(3y+2)=8(3y-2) | | -5-6n=-3(2n+3) | | -15x=-8 | | x^2+x^3+x^4+5x^2=0 | | -(5x+7)=108 | | -(5x+7)=6 | | 3/7(c+4)=4 | | -6(4+r)=18 | | 39+7x=2x-6 |